A Survey on Recommender Systems for Internet of Things: Techniques, Applications and Future Directions. (19th May 2021) - Altulyan, May; Yao, Lina; Wang, Xianzhi; Huang, Chaoran; Kanhere, Salil S; Sheng, Quan Z
Abstract: Recommendation is a critical tool for developing and promoting the benefits of the Internet of Things (IoT). In recent years, recommender systems have attracted considerable attention in many IoT-related fields such as smart health, smart home, smart tourism and smart marketing. However, traditional recommender system approaches fail to exploit ever-growing, dynamic and heterogeneous IoT data in building recommender systems for the IoT (RSIoT). This article aims to provide a comprehensive review of state-of-the-art RSIoT, including the related techniques, applications and a discussion on the limitations of applying recommendation systems to IoT. Finally, we propose a reference framework for comparing existing studies to guide future research and practices.